Developing interventions to change recycling behaviors: A case study of applying behavioral science. Issue 4 (1st October 2016) - Gainforth, Heather L.; Sheals, Kate; Atkins, Lou; Jackson, Richard; Michie, Susan
ABSTRACT: The Theoretical Domains Framework (TDF) and the Behavior Change Wheel (BCW) are frameworks that can be used to develop recycling interventions. The aim of this study was to demonstrate the utility of these frameworks for developing recycling interventions. 20 semistructured interviews with university building users were analyzed using the TDF and BCW. Environmental context and resources, beliefs about consequences, knowledge, and intention were identified as the key theoretical domains influencing recycling behaviors. The BCW was used to develop recommendations for intervention. This research is the first case study to demonstrate how the TDF and the BCW can be used to develop recycling interventions.